Pengaruh Struktur Modal, Kebijakan Dividen, dan Perencanaan Pajak Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Properti Yang Terdaftar di BEI Periode 2018-2020) - Rosyidah Nur Amalina; Afifudin Afifudin; Hariri Hariri (Universitas Islam Malang, 2023)
This study aims to examine the results of capital structure, dividend policy, and tax planning on the value of the company in the coal mining sector in 2018-2020. In this study using signal theory and agency theory, where signal theory argues that there is information asymmetry between the company and external parties because the company knows more about the company and upcoming projects than external parties. Agency theory explains that shareholders and company management have different duties and interests, where management has more information than shareholders. This study uses secondary data from the Indonesia Stock Exchange Annual Report. The type of data used in this study is quantitative. This study uses a purposive sampling method and uses multiple linear regression analysis with the help of computer software for SPSS version 22 statistics. The results show that capital structure has no effect on firm value, dividend policy has no effect on firm value, tax planning has a positive effect on firm value. Simultaneously capital structure, dividend policy, and tax planning have a significant positive effect on firm value. In this study the variables used were only able to contribute 14.9% to the value of the company, while the remaining 85.1% was influenced by other variables outside this studyKeywords : Capital structure, dividend policy, tax planning, company value.